pengaruh konsentrasi dan lama perendaman zpt daging keong mas (pomacea canaliculata l.) terhadap pertumbuhan stek lada (piper nigrum l.) - Hary Wijaya; Maimunah Maimunah; Gusmeizal Gusmeizal (Universitas Medan Area, 2019)
To improve the quality of pepper products through organic cultivation using organic growth regulators. This Research aims to investigate concentration and long immersion effect of golden snail meat (Pomacea canaliculata L.) on the growth of pepper cuttings (Piper nigrum L.). the method was experimental with a randomized block design (RAK) Factorial design with two factors namely various golden snail meat concentrations and long immersion ranging from several hours. The parameters observed in this study was Growth Percentage (%), Bud Height (cm), Number of Leaves (Strands), Root Length (cm), and Root Volume (ml). The results showed that the treatment of snail meat zpt concentration did not significantly affect the shoot height parameters but significantly affected the percentage of growth, number of leaves, root length and root volume where the effective zpt concentration was 50%. The long immersion treatment significantly affected the percentage of growth and shoot height where the best treatment at w1 was 3 hours’ immersion. The treatment combination of ZPT golden snail meat (Pomacea canaliculata L.) and long immersion did not significantly affect all observations parameters.